The amazonian capim-açú is less nitrogen dependente than antelope grass to produce leaf dry matter - Ivo G. R. de Araújo; Jairo O. Cazetta; Rosane C. Rodrigues; Sâmara S. C. Sanchês; Clésio dos S. Costa; Francisco B. F. de Sousa (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The Maranhão floodplain is dominated by native grasses like capim-açú (Paspalum plicatulum, Mich.). Due to scarce information on nutrient demands of native species, farmers are replacing native pastures by exotic and potentially invasive species such as antelope grass (Echinochloa pyramidalis, Lam). The aim of this study was to compare the growth of capim-açú and antelope grass, under varying N and K doses, to better understand the potential of capim-açú to be used as forage. The experiment was carried out in pots, consisting of a 2 × 5 × 2 factorial scheme (2 species × 5 N doses × 2 K doses) with four repetitions, in a completely randomized design. The N doses of 0, 50, 100, 150 and 200 mg dm-3 were combined with 10 and 30 mg dm-3 K2O. The capim-açú produces higher leaf to stem ratio aboveground by using lower nitrogen and potassium doses than antelope grass. Leaf, stalk, and total dry matter production of both studied species do not respond to potassium doses.